Long-read sequence assembly: a technical evaluation in barley. Issue 6 (12th March 2021) - Mascher, Martin; Wicker, Thomas; Jenkins, Jerry; Plott, Christopher; Lux, Thomas; Koh, Chu Shin; Ens, Jennifer; Gundlach, Heidrun; Boston, Lori B; Tulpová, Zuzana; Holden, Samuel; Hernández-Pinzón, Inmaculada; et al.
Abstract: Sequence assembly of large and repeat-rich plant genomes has been challenging, requiring substantial computational resources and often several complementary sequence assembly and genome mapping approaches. The recent development of fast and accurate long-read sequencing by circular consensus sequencing (CCS) on the PacBio platform may greatly increase the scope of plant pan-genome projects. Here, we compare current long-read sequencing platforms regarding their ability to rapidly generate contiguous sequence assemblies in pan-genome studies of barley ( Hordeum vulgare ). Most long-read assemblies are clearly superior to the current barley reference sequence based on short-reads. Assemblies derived from accurate long reads excel in most metrics, but the CCS approach was the most cost-effective strategy for assembling tens of barley genomes. A downsampling analysis indicated that 20-fold CCS coverage can yield very good sequence assemblies, while even five-fold CCS data may capture the complete sequence of most genes. We present an updated reference genome assembly for barley with near-complete representation of the repeat-rich intergenic space. Long-read assembly can underpin the construction of accurate and complete sequences of multiple genomes of a species to build pan-genome infrastructures in Triticeae crops and their wild relatives. Abstract : A greatly improved reference genome sequence of barley was assembled from accurate long reads.